Algorithms, allyship, and advice: A qualitative analysis of fertility tracker marketing - Kate Sheridan Clay; Sue Ziebland; John Powell (Digital Health)
Objective Proponents of ‘Femtech’, digital technology targeting women, frame them as instruments of women's empowerment that will revolutionise digital care. Its critics argue industry uses the moniker to popularise platforms that surveil reproductive data for profit. This qualitative analysis critically examines the marketing language used to promote digital interventions for managing infertility and discusses implications for users. Methods We use an inductive thematic analysis approach to assess advertising for 15 top fertility tracking applications. Using both Foucauldian critical theory and feminist theory, we identified a code set and major themes connecting marketing content to broader rhetoric around (in)fertility, gender equality, and power dynamics in health care. Results The main themes identified are: an emphasis on technological rather than human intelligence, allyship, online safety, and reliable advice. Reliance on non-human support is emphasised across multiple themes, and the framing of contested issues such as privacy and security is explored after the introduction of anti-abortion legislation in the United States, where many of the platform companies and users are based. Conclusion We demonstrate how company marketing encourages users to centre digital tracking technologies in their fertility journeys. In doing so, Femtech marketers place the complex burden of reproductive labour on women's shoulders while offering a digital reprieve (for a fee).